THE EFFECT OF SUBJECTIVE NORMS AND ATTITUDES TOWARDS PURCHASING DECISIONS THROUGH CONSUMER INTEREST IN CONSUMABLE HALAL PRODUCT (Consumer Case Study in The City of Makassar) - Awal Zulqadri Arief; Abdul Rahman Kadir; Nuraeni Kadir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
The purposes of this study are to measure (1) the effect of Subjective norms to purchase decision, (2) the effect of Attitudes to purchase decision, (3) the effect of Consumer Interest in the relation between Subjective Norms and Attitude toward Purchasing Decision. The population in this research are Muslims who lived in Makassar city with 156 samples as respondents. Path Analysis used as statistical tools to test the hypothesis. The result shows that subjective norms and attitudes significantly affect purchasing decisions and also through consumer interest significantly affects purchasing decisions in the consumable halal product.